Sugar and Aldehyde Content in Flavored Electronic Cigarette Liquids. Issue 8 (22nd November 2017) - Fagan, Pebbles; Pokhrel, Pallav; Herzog, Thaddeus A; Moolchan, Eric T; Cassel, Kevin D; Franke, Adrian A; Li, Xingnan; Pagano, Ian; Trinidad, Dennis R; Sakuma, Kari-lyn K; Sterling, Kymberle; Jorgensen, Dorothy; et al.
Abstract: Introduction: Sugars are major constituents and additives in traditional tobacco products, but little is known about their content or related toxins (formaldehyde, acetaldehyde, and acrolein) in electronic cigarette (e-cigarette) liquids. This study quantified levels of sugars and aldehydes in e-cigarette liquids across brands, flavors, and nicotine concentrations ( n = 66). Methods: Unheated e-cigarette liquids were analyzed using liquid chromatography mass spectrometry and enzymatic test kits. Generalized linear models, Fisher's exact test, and Pearson's correlation coefficient assessed sugar, aldehyde, and nicotine concentration associations. Results: Glucose, fructose and sucrose levels exceeded the limits of quantification in 22%, 53% and 53% of the samples. Sucrose levels were significantly higher than glucose [χ 2 (1) = 85.9, p < .0001] and fructose [χ 2 (1) = 10.6, p = .001] levels. Formaldehyde, acetaldehyde, and acrolein levels exceeded the limits of quantification in 72%, 84%, and 75% of the samples. Acetaldehyde levels were significantly higher than formaldehyde [χ 2 (1) = 11.7, p = .0006] and acrolein [χ 2 (1) = 119.5, p < .0001] levels. Differences between nicotine-based and zero-nicotine labeled e-cigarette liquids were not statistically significant for sugars or aldehydes. We found significant correlations between formaldehyde and fructose (−0.22, p = .004) and sucrose (−0.25, p = .002) and acrolein and fructose (−0.26, p = .0006) and sucrose (−0.21, p = .0006). There were no significant correlations between acetaldehyde and any of the sugars or any of the aldehydes and glucose. Conclusions: Sugars and related aldehydes were identified in unheated e-cigarette liquids and their composition may influence experimentation in naïve users and their potential toxicity. Implications: The data can inform the regulation of specific flavor constituents in tobacco products as a strategy to protect young people from using e-cigarettes, while balancing FDA's interest in how these emerging products could potentially benefit adult smokers who are seeking to safely quit cigarette smoking. The data can also be used to educate consumers about ingredients in products that may contain nicotine and inform future FDA regulatory policies related to product standards and accurate and comprehensible labeling of e-cigarette liquids.